TURKISH-AMERICAN RELATIONS WITHIN THE TRIANGLE OF MISSIONARY WORK, COMMERCIAL ACTIVITIES, AND COMMUNISM IN INTERWAR PERIOD - Hakan GÜNGÖR (Fırat University, 2019)
Turkish-American relations were built on a similar democratic ideology. While democracy brought the United States and Turkey closer in the early 1920s and thereafter, the attitude of Turkish government against Communism during the First Red Scare in the U.S. assured Americans that Turkey was a trustworthy ally because it shared common democratic values. Although the abolition of Sultanate and caliphate and declaration of a republican form of government determined the democratic direction of the Turkish nation, the Turkish government’s position against communism between 1920 and 1938, which US officials closely watched and reported to the White House, established long lasting friendly relations between the United States and Turkey. This bilateral relationship reached its peak during the Second World War and the Cold War. While historians' works about early US-Turkish relations largely revolves around missionary activities and to some extent economic and financial interactions, the US archival dossiers and documents reveal the importance of the Turkish government’s attitudes against communism in this friendly relationship. Therefore, this study looks at Turkish-American relations within the triangle of missionary work, commercial activities, and communism between 1920 and 1938.